Risk Factors of Developmental Defects of Enamel-A Prospective Cohort Study - Wong, Hai Ming; Peng, Si-Min; Wen, Yi Feng; King, Nigel M.; McGrath, Colman P. J. (PloS one, 2014)
Current studies on the aetiology of developmental defects of enamel (DDE) are subject to recall bias because of the retrospective collection of information. Our objective was to investigate potential risk factors associated with the occurrence of DDE through a prospective cohort study. Using a random community sample of Hong Kong children born in 1997, we performed a cohort study in which the subjects' background information, medical and dental records were prospectively collected. A clinical examination to identify DDE was conducted in 2010 when the subjects were 12 years old. The central incisor, lateral incisor and first molar in each quadrant were chosen as the index teeth and were examined 'wet' by two trained and calibrated examiners using the modified FDI (DDE) Index. With a response rate of 74.9%, the 514 examined subjects had matched data for background information. Diffuse opacites were the most common type of DDE. Of the various possible aetiological factors considered, only experience of severe diseases during the period 0-3 years was associated with the occurrence of 'any defect' (p = 0.017) and diffuse opacities (p = 0.044). The children with experience of severe diseases before 3 years of age were 7.89 times more likely to be affected by 'any defect' compared with those who did not have the experience (OR 7.89; 95% CI 1.07, 58.14; p = 0.043). However, after adjusting for confounding factors, the association no longer existed. No variables could be identified as risk factors of DDE in this Hong Kong birth cohort.